2015 Digital Heritage 2015
DOI: 10.1109/digitalheritage.2015.7419587
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Laboratory An immersive VR experience to spread ancient libraries heritage

Abstract: This paper presents the evolving embodiments of “A Virtual Laboratory”, a VR-based videogame simulating an experiment of medical distillation in a medieval alchemy lab. Players are encouraged to acquire the knowledge needed to master the operations to be performed by consulting the digital representation of an ancient treatise on distillation hosted at the Gunnerus Library of Trondheim, The game is part of a larger project called MUBIL aimed at disseminating the knowledge of the Library's collections of ancien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Formative approaches mainly gather user opinions (e.g. about perceived usability) and qualitative observations by researchers, like the work of Lorenzini et al (2015) who evaluate a VR-based videogame simulating an experiment of medical distillation in a medieval alchemy lab with having users play the game and then answer a questionnaire and provide a post-hoc interview. In summative approaches conclusions are drawn based on measures of user performance or logged user actions.…”
Section: Methods Of Empirical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Formative approaches mainly gather user opinions (e.g. about perceived usability) and qualitative observations by researchers, like the work of Lorenzini et al (2015) who evaluate a VR-based videogame simulating an experiment of medical distillation in a medieval alchemy lab with having users play the game and then answer a questionnaire and provide a post-hoc interview. In summative approaches conclusions are drawn based on measures of user performance or logged user actions.…”
Section: Methods Of Empirical Evaluationmentioning
confidence: 99%
“…of publications Anagnostakis et al 2016;Andreoli et al 2016;Arends et al 2012;Bellotti et al 2012;Bellucci et al 2015;Callaway et al 2014;Chalvatzaras et al 2014;Coenen et al 2013;Correia et al 2014;Creed et al 2013;Di Franco et al 2015;. Diaz et al 2014;Duguleana et al 2016;Falvo, 2015;Floch and Jiang 2015;Froschauer et al 2013;Georgiadi et al 2016;Graf et al 2015;Han et al 2014;Huang et al 2013;Ijaz et al 2016;Jylhä et al 2015; Kassapakis et al 2016;Katsouri et al 2015;Kennedy et al 2013;Koutsabasis and Vosinakis, 2016;Loizides et al 2014;Lorenzini et al 2015; Madsen and Madsen, 2015;Maina and Suleman, 2015;Marshall et al 2016;Marton et al 2014;McCaffery et al 2015;O'Keefe and Benyon, 2015;O'Sullivan et al 2014;Panayiotou and Lanitis, 2016;Pietroni and Adami, 2014;Rennick-Egglestone et al 2016;Reunanen et a;2015;Rizvić and Skalonjić 2015; Rojas et al 2015;Rubino et al 2015;Shih et al 2015;…”
mentioning
confidence: 99%
“…A virtual laboratory provides multiple users with continuous and simultaneous access to learn an experiment process via a remote server [7,27]. By simulating the experimental process and experimental phenomena on the network, users can experience the experiment operation procedures, understand the experiment data, and observe the results in an immersive and visible virtual environment . In addition, survey has shown that virtual experiments have higher device availability and a higher degree of openness, while the educational value of virtual and on‐site laboratory experiences is comparable based on student performance .…”
Section: Introductionmentioning
confidence: 99%
“…These ambiences are very evocative for people and also music plays an important role to let the spectators get lost in the virtual world as much as possible. to look at, sometimes it is also possible to interact with animated character and to "grab" objects and playing with them [8]. The characteristic of serious games is not only to entertain the user, but to teach and to let the user easily assimilate the fundamental aspects of several past cultures 3 .…”
Section: Table Of Figuresmentioning
confidence: 99%
“…Very recently, also some applications of virtual archaeology and virtual heritage have been developed to be performed through a head mounted display [8], [11], [132]. In particular, a very good free mobile application for Google Cardboard have been made…”
Section: Virtual Reality Applicationmentioning
confidence: 99%